Potential and Management Strategy of Small Pelagic Resources in Tomini Gulf - Cahniar Djamil (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
The purpose of this study was to determine the potential and level of utilization and develop a strategy for developing the small pelagic fisheries resources in Tomini Gulf in Gorontalo Province. The method used in this study using a surplus production model from Schaefer and Fox and a study of the strategy of developing small pelagic fisheries resource using SWOT analysis. The results showed that the level of utilization of small pelagic fisheries resources in Tomini Gulf was still under fishing. Using the Schaefer model, an estimated Maximum Sustainable Yield (MSY) of 29.660 tons / year was obtained with an optimal effort of 4.8240 trips / year which was equivalent to 168 purse seiners. Using the Fox model, an estimated Maximum Sustainable Yield (MSY) of 24,300 tons / year was estimated with an optimal effort of 44,000 trips / year which is equivalent to 153 purse seiners. The main thing that needs to be done in the strategy of developing small pelagic fishery resource utilization in Tomini Gulf is to improve fishing operations by adding various types of fishing gear, so as to enable fishing to be more effective and intensive, increase added value of the catch so that fishermen can sell their catch to fish processing plants at best prices. Keywords: Potential; management strategy; small pelagic; Tomini Gulf.